2013
DOI: 10.2478/hukin-2013-0064
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method of Key-Frame Extraction Based on a Cluster Algorithm

Abstract: The purpose of the present study was to investigate the effects of different configurations of repetitions within a set of deadlifts on the mechanical variables of concentric force, concentric time under tension, impulse, work, power, and fatigue. Eleven resistance trained men (age: 21.9 ± 1.0 years; deadlift 1 repetition maximum: 183.2 ± 38.3 kg) performed four repetitions of the deadlift exercise with a load equivalent to 90% of 1 repetition maximum under three different set configurations: Traditional (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…Since the relative external load was the same during each protocol, there was no difference in MF between protocols, in line with previous research ( Denton and Cronin, 2006 ; Moir et al, 2013 ; Tufano et al, 2016b ). There is a lack of PF data within the cluster set literature, but previously, Hardee et al (2012) showed that PF was better maintained when longer inter-repetition rest periods were used during three cluster sets of six power cleans performed with a load of 80% of 1RM.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Since the relative external load was the same during each protocol, there was no difference in MF between protocols, in line with previous research ( Denton and Cronin, 2006 ; Moir et al, 2013 ; Tufano et al, 2016b ). There is a lack of PF data within the cluster set literature, but previously, Hardee et al (2012) showed that PF was better maintained when longer inter-repetition rest periods were used during three cluster sets of six power cleans performed with a load of 80% of 1RM.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, PF remained fairly steady during RR1, but was greater during successive repetitions compared to the first repetition of each 4-repetition segment in RR4 and CS4 ( Figure 2c ). Despite this being the first study to compare PF between individual repetitions of the back squat using cluster sets, the results from a previous study may shed light on this PF phenomenon ( Moir et al, 2013 ). In a study conducted by Moir et al (2013) , participants performed four repetitions of the deadlift in a row (i.e.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations